Cargo-free immunomodulatory nanoparticles combined with anti-PD-1 antibody for treating metastatic breast cancer. (February 2021) - Zhang, Yining; Hughes, Kevin R.; Raghani, Ravi M.; Ma, Jeffrey; Orbach, Sophia; Jeruss, Jacqueline S.; Shea, Lonnie D.
Abstract: The presence of immunosuppressive innate immune cells such as myeloid derived suppressor cells (MDSCs), Ly6C-high monocytes, and tumor-associated macrophages (TAMs) at a tumor can inhibit effector T cell and NK cell function. Immune checkpoint blockade using anti-PD-1 antibody aims to overcome the immune suppressive environment, yet only a fraction of patients responds. Herein, we test the hypothesis that cargo-free PLG nanoparticles administered intravenously can divert circulating immune cells from the tumor microenvironment to enhance the efficacy of anti-PD-1 immunotherapy in the 4T1 mouse model of metastatic triple-negative breast cancer. In vitro studies demonstrate that these nanoparticles decrease the expression of MCP-1 by 5-fold and increase the expression of TNF- α by more than 2-fold upon uptake by innate immune cells. Intravenous administration of particles results in internalization by MDSCs and monocytes, with particles detected in the liver, lung, spleen, and primary tumor. Nanoparticle delivery decreased the abundance of MDSCs in circulation and in the lung, the latter being the primary metastatic site. Combined with anti-PD-1 antibody, nanoparticles significantly slowed tumor growth and resulted in a survival benefit. Gene expression analysis by GSEA indicated inflammatory myeloid cell pathways were downregulated in the lung and upregulated in the spleen and tumor. Upregulation of extrinsic apoptotic pathways was also observed in the primary tumor. Collectively, these results demonstrate that cargo-free PLG nanoparticles can reprogram immune cell responses and alter the tumor microenvironment in vivo to overcome the local immune suppression attributed to myeloid cells and enhance the efficacy of anti-PD-1 therapy.